2021
DOI: 10.3389/fcimb.2021.670211
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Microbial Community of Accumulated Biofilm in Dental Unit Waterlines of Different Specialties

Abstract: The contamination of dental unit waterlines (DUWLs) is a serious problem and directly affects the dental care. This study aims to explore the microbial community of biofilm in DUWL from different specialties and investigate the associated factors. A total of 36 biofilm samples from 18 DUWL of six specialties (i.e., prosthodontics, orthodontics, pediatrics, endodontics, oral surgery, and periodontics) at two time points (i.e., before and after daily dental practice) were collected with a novel method. Genomic D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 50 publications
3
8
2
Order By: Relevance
“…In our study, the dominant bacteria at the phylum level were Proteobacteria representing over 91% of the total sequences, which was similar to the results of previous reports [ 14 , 15 , 18 ]. Unsurprisingly, Proteobacteria was a commonly detected phylum in water distribution systems, owing to high tolerance to chlorine [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, the dominant bacteria at the phylum level were Proteobacteria representing over 91% of the total sequences, which was similar to the results of previous reports [ 14 , 15 , 18 ]. Unsurprisingly, Proteobacteria was a commonly detected phylum in water distribution systems, owing to high tolerance to chlorine [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…Previous reports have informed several environmental factors associated with biofilm accumulation, such as the age of dental unit [ 21 ], disinfectants [ 10 , 13 ], and specialty and daily dental practices [ 15 ]. However, in this study, despite the 29 samples compared in different groups, no significant differences among these samples as shown by alpha diversity indices and the PCoA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that biofilm in DUWLs is related to dental specialty with more abundance of bacterial and fungi communities. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms colonizing DUWL are generally non-pathogenic aerobic and heterotrophic environmental bacteria. However, occasionally, pathogenic and/or opportunistic pathogens such as Pseudomonas , Legionella and Mycobacterium species are found ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%